The influence of library club membership in the choice of BLIS as a college major - Carlos, Ma. Teresa Consuelo Francisca E.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This study is about the influence of Library Club membership in the choice of Bachelor of Library and Information Science as a college major and the objectives are set to determine if the choice or non-choice of BLIS as a college major depend on the member or non-membership in Library Club in high school and if the Library club membership status affects the mode of entry to BLIS. This study was divided into two (2) parts, thus it needed two (2) sets of populations. For the first part of the study, both male and female graduating high school students for AY 2000-2001 from two (2) private schools in Pampanga and (2) private schools in Metro Manila which have Library Club or Book Lovers'Club as one of the schools' organization were the basis for the population used. As for the second part, the BLIS enrolled students of the Institute of Library Science, University of the Philippines Diliman was used. The research instrument used was the survey method while the chi-square analysis was used for both parts of the study. The findings of the study were that Library Club membership status and the choice of BLIS are independent and the Library Club membership status and BLIS mode of entry are likewise independent.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines. Institute of Library Science -- Students; Library clubs